Mechanical Instabilities and the Mathematical Behavior of van der Waals Gases - Pennini, Flavia Catalina (2024)
We explore the mathematical behavior of van der Waals gases at temperatures where classical descriptions are inadequate due to emerging quantum effects. Specifically, we focus on temperatures 2 at which the thermal de Broglie wavelength becomes comparable to the interparticle spacing, signifying the onset of quantum mechanical influences. At such temperatures, we find that the isothermal compressibility of the gas becomes negative, indicating mechanical instability. In the pressure–density diagrams, we note that the pressure can become negative at small densities, illustrating the limitations of classical models and the necessity for quantum mechanical approaches. These phenomena serve as clear indicators of the transition from classical thermodynamics to quantum statistical mechanics. The observed mechanical instability and negative pressures represent rare macroscopic manifestations of quantum effects, demonstrating their profound impact on gas behavior. Our study highlights the significant role of emerging quantum properties on observable macroscopic scales, particularly for van der Waals gases at low temperatures and small densities. Additionally, we discuss the theoretical implications of our findings, underlining the limitations of the van der Waals model under extreme conditions and emphasizing the critical need to include quantum corrections in thermodynamic frameworks.